An Analysis of Advance Level Students to Perform Their Speaking English - Harya, Trisna Dinillah (CV. Creative Tugu Pena, 2022)
This research aimed to identify and to describe about the students’ problem when they speak English. Because the advanced level Student of University couldn’t speak English well when they perform their Proposal Seminar and also final examination at Institut Agama Islam Negeri Metro Lampung. The data were taken by interview with 20 students, and questionnaire. The participants were students of English study program. The result showed that most students from advanced level student couldn’t speak English well when they presented seminar proposal and final examination or munaqosyah. Because they were too worry about making mistakes on their performance and because they don’t have enough vocabulary and grammar mstery so it would give impact to their pronunciation and confidence. Keywords: Advance Students Speaking, Speaking Skill, Speaking Perform